Dibenzofuran Synthesis: Decarbonylative Intramolecular C−H Arylation of Aromatic Esters. Issue 7 (6th June 2018) - Okita, Toshimasa; Komatsuda, Masaaki; Saito, Ami N.; Hisada, Tomoya; Takahara, Tomoaki T.; Nakayama, Keito P.; Isshiki, Ryota; Takise, Ryosuke; Muto, Kei; Yamaguchi, Junichiro
Abstract: A method to provide dibenzofurans through decarbonylative C−H arylation is described. Diaryl ethers bearing an ester functional group, which can be readily prepared by a SN Ar reaction, underwent intramolecular C−H arylation in the presence of a palladium catalyst to afford the corresponding dibenzofurans. Electron‐rich bis(dialkylphosphine)s such as dcype were critical as the ligand, otherwise the reactions did not proceed at all. This is the first example of C−H arylation of aromatic esters with simple arenes utilized in intramolecular fashion. Abstract : Deciphering the code : Dibenzofurans were synthesized by palladium‐catalyzed decarbonylative C−H arylation, wherein electron‐rich bis(dialkylphosphine)s such as 1, 2‐bis(dicyclohexylphosphino)ethane (dcype) were critical as the ligand.